Mapping poverty and livestock in the developing world - Thornton, Philip K.; Kruska, Russell L.; Henninger, N.; Kristjanson, Patricia M.; Reid, Robin S.; Atieno, F.; Odero, A.N.; Ndegwa, T. (International Livestock Research Institute, 2002)
This study produces a set of maps and tables that locate significant populations of poor livestock keepers and has broadly assessed how poor livestock keeping populations are likely to change over the next 3-5 decades. The outputs of the study are based on innovative analysis using new global data sets. This includes mapping a global livestock production system classification, using definitions based on agroclimatology and human population density; mapping human population growth scenarios to 2050 for sub-Saharan Africa (SSA), Central and South America (CSA), and Asia; development of climate surfaces for Africa to 2050 as predicted from the downscaling of results from coarse-resolution global climate change models; mapping the livestock system classification for Africa to 2050 as driven by predicted changes in human population and climate; mapping district - and province - level poverty data for Kenya, Tanzania and Uganda as an example of high-resolution poverty data for more effective targeting of development assistance. Major conclusions of the analysis are outlined at the end of the document.